Proceedings of the 2015 ACM SIGCHI Conference on Creativity and Cognition 2015
DOI: 10.1145/2757226.2757253
|View full text |Cite
|
Sign up to set email alerts
|

A Modular Approach to Promote Creativity and Inspiration in Search

Abstract: When searching through collections of books or written texts, the efficient yet limiting query paradigm is still the most dominant entry point. Previous work characterizes search processes in various contexts and describes them as integral and closely related to creative endeavours. We revisit this work from a design perspective, proposing guidelines for versatile search interfaces that are based on a modular approach to search. Inspired by aspects of search in physical environments, our recommendations addres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
(137 reference statements)
1
3
0
Order By: Relevance
“…Previous research has characterized search strategies in digital systems as a combination of querying, assessment, and selection activities [1,13,40]. We found our participants' search workflow on both search systems to be consistent to these previous findings.…”
Section: General Approaches To Media Searchsupporting
confidence: 89%
See 2 more Smart Citations
“…Previous research has characterized search strategies in digital systems as a combination of querying, assessment, and selection activities [1,13,40]. We found our participants' search workflow on both search systems to be consistent to these previous findings.…”
Section: General Approaches To Media Searchsupporting
confidence: 89%
“…When designing our in-situ search system, we followed designcentered models of the search process [40], as well as contemporary guidelines toward designing search interfaces [16,46]. Hearst and Wilson, for example, both highlight the need of supporting the fluid adjustment of search criteria, and establishing a close connection between search criteria and the result list [16,46].…”
Section: Designing (Library) Search Interfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…Their findings revealed the need to develop electronic resources supporting information seeking, interpretation, and use to enhance students' creativity. Thudt et al (2015) analyzed people's book search habits and identified four micro-strategies (querying, linking, scanning, and assessing) as search process modules. Their findings indicated opportunities for linking learning, creativity, and ideation.…”
Section: Creativity and Search Processesmentioning
confidence: 99%